Effect of prolonged exercise on arterial oxygen saturation in athletes susceptible to exercise-induced hypoxemia - Stewart, I. B.; Pickering, R. L. (Scandinavian Journal of Medicine & Science in Sports, 2007)
This study examined the effect of prolonged endurance exercise on the development of exercise-induced hypoxemia (EIH) in athletes who had previously displayed EIH during an incremental maximal exercise test. Five male and three female endurance-trained athletes participated. Susceptibility to EIH was confirmed through a maximal incremental exercise test and defined as a reduction in the saturation of arterial oxygen (SpO2) of =4% from rest. Sixty minutes of running was conducted, on a separate day, at an oxygen consumption corresponding to 95% of ventilatory threshold. Immediately following the 60 min exercise bout, athletes commenced a time trial to exhaustion at 95% maximal oxygen consumption (VO2max). The reduction in SpO2 was significantly greater during the maximal incremental test, than during the 60 min, or time trial to exhaustion (-8.8±1.4%, -3.3±1.1%, and -4.1±2.3%, P<0.05, respectively). The degree of desaturation during the 60 min was significantly related to the relative intensity of exercise at 95% ventilatory threshold (adjusted r2=0.54, P=0.02). In conclusion, athletes who did not exercise at greater than 73% VO2max during 60 min of endurance exercise did not display EIH, despite being previously susceptible during an incremental maximal test.